Pemaknaan Agama sebagai Hasil Interaksi Antar Anggota Komunitas Punk Muslim di Indonesia - PRIMAGARA, MEGI (Komunikator, 2014)
The meaning of religion for someone can be influenced by interactions with other people. It could be seen from the result of the research towards the members of Punk-Moslems community. When they stay in punk community where most members see religion as something which is unimportant and communicate this matter to the other members, they also see religion in the same way as the other members do. On the other hand, when they stay with Punk-Moslems community that sees religion as the most important thing in life and communicate this matter to the other members, they can aslo change their view towards religion. The process of interaction with other individuals can get someone to construct the meaning of something. Keywords: interaction process between individuals, religion realization, symbolic interaction theory